Perspectives on Element Theory - Bendjaballah, Sabrina; Tifrit, Ali; Voeltzel, Laurence 1987-; Backley, Phillip; Dresher, B. Elan; Hulst, Harry van der; Kula, Nancy C.; Nasukawa, Kuniya; Pöchtrager, Markus A.; Raimy, Eric; Riemsdijk, Henk van; Youngberg, Connor (Studies in generative grammar ;, 2021)
Element Theory (ET) covers a range of approaches that consider privativity a central tenet defining the internal structure of segments. This volume provides an overview and extension of this program, exploring new lines of research within phonology and at its interface (phonetics and syntax). The present collection reflects on issues concerning the definition of privative primes, their interactions, organization, and the operations that constrain phonological and syntactic representations. The contributions reassess theoretical questions, which have been implicitly taken for granted, regarding privativity and its corollaries. On the empirical side, it explores the possibilities ET offers to analyze specific languages and phonological phenomena.